Incidencia del proceso contable-financiero en la toma de decisiones en la Parroquia San Juan XXIII del cantón Durán, periodo 2023. - Davalos Rivera, Mariuxi Marina (2024)
The purpose of this study is to analyze the impact of accounting and financial processes on decision-making within the San Juan XXIII Parish of the Durán canton, for the period 2023. The hypothesis presented states that efficient accounting and financial processes can lead to positive results that would influence the administrative and operational decisions of the parish, therefore, the information entered must be real and in accordance with the necessary civil and ecclesiastical accounting standards and policies. The San Juan XXIII parish of the Durán canton, headquarters of this process, faces all the challenges, including: the lack of accounting knowledge, analysis and interpretation by the staff and modern tools that are costly for society in their management and for the projects to be developed that negatively impact the decision-making of social actors. These are the aspects that must be evaluated in order to make improvements and be able to manage better, in order to enhance the local decision-making process. Evidence of this impact will be obtained through the content analysis process carried out by collecting information, using various techniques, through observation and interviews. The analysis will allow us to find the accounting practices and their interaction with financial and resource management practices, which are key to decision-making. This review will allow committee members to gain knowledge about the processes for the 2023 period and, consequently, achieve the project goals, suggesting future strategies that will be aimed at increasing income.